Is There a Role for an 18F-fluorodeoxyglucose-derived Biological Boost in Squamous Cell Anal Cancer?. Issue 2 (February 2019) - Sabbagh, A.; Jacobs, C.; Cooke, R.; Chu, K.-Y.; Ng, S.M.; Strauss, V.Y.; Virdee, P.S.; Hawkins, M.A.; Aznar, M.C.; Muirhead, R.
Abstract: Aims: To investigate the potential role for a biological boost in anal cancer by assessing whether subvolumes of high 18F-fluorodeoxyglucose (FDG) avidity, identified at outset, are spatially consistent during a course of chemoradiotherapy (CRT). Materials and methods: FDG-positron emission tomography (FDG-PET) scans from 21 patients enrolled into the ART study (NCT02145416) were retrospectively analysed. In total, 29 volumes including both primary tumours and involved nodes >2 cm were identified. FDG-PET scans were carried out before treatment and on day 8 or 9 of CRT. FDG subvolumes were created using a percentage of maximum FDG avidity at thresholds of 34%, 40%, 50%, on the pre-treatment scans, and 70% and 80% on the subsequent scans. Both FDG-PET scans were deformably registered to the planning computed tomography scan. The overlap fraction and the vector distance were calculated to assess spatial consistency. FDG subvolumes for further investigation had an overlap fraction >0.7, as this has been defined in previous publications as a 'good' correlation. Results: The median overlap fractions between the diagnostic FDG-PET subvolumes 34%, 40% and 50% of maximum standardised uptake value (SUVmax ) and subsequent FDG-PET subvolumes of 70% of SUVmax were 0.97, 0.92 and 0.81. The median overlap fraction between the diagnostic FDG-PET subvolumes 34%, 40% and 50% and subsequent FDG-PET subvolumes of 80% were 1.00, 1.00 and 0.92. The median (range) vector distance values between diagnostic FDG-PET subvolumes 34%, 40% and 50% and subsequent FDG-PET subvolumes of 80% were 0.74 mm (0.19–2.94) 0.74 mm (0.19–3.39) and 0.71 mm (0.2–3.29), respectively. Twenty of 29 volumes (69.0%) achieved a threshold > 0.7 between the FDG 50% subvolume on the diagnostic scan and the FDG 80% subvolume on the subsequent scan. Conclusion: FDG-avid subvolumes identified at baseline were spatially consistent during a course of CRT treatment. The subvolume of 50% of SUVmax on the pre-treatment scan could be considered as a potential target for dose escalation. Highlights: A biological boost at diagnosis is spatially consistent during chemoradiotherapy. Threshold of 50% SUVmax has been suggested as a potential boost volume. Biological boost in anal cancer should be further investigated in clinical trials.